Feelings of guilt when a sample of divorced women - Abdul Nabi Al-Abadi, Hana (Journal of College of Education, 2021)
The current research aims to identify the feeling of guilt among a sample of divorced women in Basra Governorate for the academic year (2019-2020) and the number of the sample members was (100) divorced women, and the research required building a tool to measure guilt, and the scale consists of (20) paragraphs, and four Alternatives (always, sometimes, rarely, never) and apparent honesty was achieved by presenting it to (6) experts in the field of psychology and psychological counseling, and the acceptance rate was (100%). Significance (0.01), and the research found that: Divorced women have a conscious feeling of guilt based on the determinants imposed by the current study tools, the size, representation and characteristics of the individuals of the research sample and the calculated T value (15,690) compared to the tabular value (1.98) at the level of significance ( 0.05), the degree of freedom (99), and the arithmetic mean (60.863) is greater than the hypothetical mean of (50).
Keywords: guilt, divorced women